"Living room art" and the material culture of provenance: Retracing bourgeois everyday life and art collecting practices through restitution files. Issue 3 (August 2021) - Löffler, Emily
Abstract: The Landesmuseum Mainz holds a bundle of objects (paintings, works on paper, furniture) that entered its collections in September 1943 as a transferral ordered by the Oberfinanzpräsident of the State of Hesse. The objects had been confiscated by the fiscal authorities of Mainz and Darmstadt immediately after their owners had been deported. In terms of artistic quality, these pieces could be described as "living room art, " a term that well reflects the social function of Jewish upper-middle-class material culture. By combining the methodologies of provenance research and material culture studies, this article analyzes how the "living room art" that once belonged to the German Jewish middle-class closely related to social belonging, self-representation, and the identity of their owners and how the anti-Semitic persecution impacted their material life. This approach aims at reframing object-based provenance research – which is traditionally formulated in the context of the "art world, " for example, the study of art dealership, collecting, and museum history – in the context of the study of Jewish middle-class cultural consumption, small-scale private art collecting, and micro-history.